Culture, communication and persuasion on gastronomic tourism websites: A multimodal analysis. Issue 3 (1st October 2020) - Turra, Elisa
Abstract: This paper examines the communicative and persuasive strategies adopted on three websites promoting gastronomic tourism: Slowfood.com/travel, Lonelyplanet.com and DeliciousItaly.com. The analysis focuses on both the visual and linguistic features used to construct the identity of Piedmont and of the tourist as well as on the interplay between verbal and non-verbal features. Hypertexts and interactive websites rely on a wide spectrum of multimodal resources and strategies to provide potential tourists with a full immersion in a given country and its culture. The ultimate goal is to sell a holiday experience by describing a reality which will be perceived as authentic and unique. In this perspective, a multi-method approach has been adopted as the analytical framework: it draws on Kress and van Leeuwen's visual grammar, Martin's semantic categories of evaluation and is unified by an overarching systemic functional theoretical framework. Discourse analysis will be combined with Quan and Wang's model of the tourist experience, in order to shed light on the correlation between communicative and persuasive features, as well as the social and discursive construction of the identity of prospective tourists and destinations.